PENERAPAN KEBIJAKAN PENDIDIKAN "PROGRAM INDONESIA PINTAR" DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Wahdania Suardi; Eko Priyo Purnomo; Lubna Salsabila (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
This article discusses Smart Indonesia Program Education Policies in the Perspective of Sustainable Development in Indonesia. A qualitative research approach based on social phenomena and human problems. In data collection, the authors obtained from literature studies in the form of online media coverage, the most recent websites, scientific articles of previous research, and government reports through the Ministry of Education and Culture of the Republic of Indonesia. The findings of this study is that the drop-out figure had never been reached last year. Five out of 1,000 primary school students dropped out of school in 2017. However, this number is increasing at the secondary school level. That is, 30 out of 1,000 children drop out of school. Four out of 1,000 primary school students dropped out of school in 2019. However, this number is increasing at the high school level, where 18 out of 1,000 children drop out of school. Thus, the Smart Indonesia policy has not been able to become a sustainable development solution in the education sector because Indonesia did not reach the minimum drop goal last year